RUSSIAN NUCLEAR NARRATIVE IN RT AND CNN (Innovative Technologica: Methodical Research Journal, 2023)
The Russian nuclear narrative as portrayed in RT (Russia Today) and CNN (Cable News Network) has been a subject of interest in recent times, given the increasing geopolitical tensions between Russia and the West. RT, being a state-owned media outlet, often focuses on highlighting the strength and advancement of the Russian military, particularly the nuclear forces. On CNN, as a privately owned American news outlet, often covers the issue of Russian nuclear capabilities from a more critical perspective, focusing on concerns about the potential risks and threats posed by the Russian nuclear arsenal.